An PEMANFAATAN LIMBAH SAYUR DARI PASAR BANYUASRI SEBAGAI PUPUK ORGANIK CAIR UNTUK PERTUMBUHAN BAWANG MERAH - Nia Erlina; Bartolomeus Kristi Brahmantia Putra; Ni Wayan Putri Juniantari; Komang Cantika Mahadewi; Awang Yonar Prakosa (Jurnal Penelitian Pertanian Terapan, 2025)
The utilization of vegetable waste as a raw material for liquid organic fertilizer (LOF) is an eco-friendly innovation that can enhance soil fertility and plant growth. This study aims to evaluate the effectiveness of LOF derived from vegetable waste from Banyuasri Market, Buleleng Regency, on the growth of shallots (Allium cepa). The study employed a Completely Randomized Design (CRD) with three treatments: Formula A (liquid concentration at 2 ml/L), Formula B (liquid concentration at 5 mL/L), and a control group (without LOF). The observed parameters included leaf length and the number of leaves over a six-week observation period. The results showed that LOF treatments (Formula A and B) led to better shallot growth compared to the control group. The average leaf length in Formula A reached 45 cm, Formula B 40 cm, while the control group only achieved 30 cm. Similarly, the number of leaves followed the same trend, with Formula A producing approximately 20 leaves, Formula B 18-19 leaves, and the control group only 15 leaves. These findings indicate that LOF derived from vegetable waste significantly enhances the vegetative growth of shallots compared to plants that did not receive additional treatment. In conclusion, the application of LOF from vegetable waste can serve as an effective organic fertilizer alternative to improve shallot growth with best concentration at 5 mL/L. The use of LOF from vegetable waste also has the potential to reduce environmental pollution while promoting sustainable agricultural productivity.